Assessment of Pregnancy Outcomes with Maternal Age: A Retrospective Study - Balihallimath, Rupa L.; Jayalaxmi, M. K.; Gan, Anita M.; Tyagi, Naresh Kumar (Current Innovations in Medicine and Medical Science Vol. 2, 2022)
This study specifies the percentile growth trajectory of placenta and new-born in different maternal age groups. One of the key determinants of a successful pregnancy result is maternal age. Extremes in maternal age will have a negative impact on the fetal and placental growth patterns. This study was conducted on 391 placentae of consecutive deliveries from the Obstetrics and Gynaecology unit of teaching Hospital from North Karnataka, India, for a period of six months. Age-wise distribution of 391 mothers reveals that 7.2 percents were less than 20 years of age and 7.6 percent more than 30 years and above, with mean 23.6 and SD 3.7 years. Percentiles of the birth weight and placental morphometry did not show any consistent relationship with increasing groups of maternal age. The study conveys that in different groups of maternal age percentiles of birth weight exhibited consistent increasing trends only in higher percentiles (75th to 95th) whereas, percentiles of placental morphometry did not exhibit consistent relationship with maternal age. Percentiles of placental morphometry did not exhibit a consistent relationship with maternal age, except the 5th and 50th percentile of placental weight and 25th percentile of placental surface area.